ANALISIS YURIDIS ATAS TUGAS DAN FUNGSI OTORITAS JASA KEUANGAN DALAM MELINDUNGI KONSUMEN JASA KEUANGAN - Saryo Saryo; Bismar Nasution; Suhaidi Suhaidi; Mahmul Siregar (USU LAW JOURNAL, 2017)
ABSTRACT Otoritas Jasa Keuangan (OJK) founded in accordance with the Undang-Undang No.21 Tahun 2011 tentang Otoritas Jasa Keuangan having task and function to regulate and control of finance institution as well as provide protection for consumer. The consumer protection given by OJK is aimed at creating a reliable consumer protection, increasing consumer empowerment, as well as raising awareness of financial service provider on the importance of consumer protection so that it increases people’s trust in financial service sector. The research problems are as folows: How the law in Indonesia regulates duties, functions, and authorities of the OJK in providing protection to consumer? How the consumer protection system in the financial services thar has been established and implemented by OJK? How is the implementation of the consumer protection system in the financial services by OJK? The results of the research showed, it is revealed that in addition to its function to regulate and control finance institution, it also protects consumer. OJK has established system of consumer protection which is integrated and supported with satisfactory and traceable feature of consumer service for complaining about financial service provider and consumer that is Financial Customer Care (FCC). Consumer protection provided by OJK consists of preventive consumer protection aimed at prevent consumer loss and repressively. Preventive consumer protection includes providing information and education for people, preparing sets of consumer protection, complaint services, market conduct regulation and other regulation conducted to prevent consumer and people loss potentials. Increase of consumer protection effectiveness provided by OJK should keep being maintained both from structure and law substance by considering condition of law tradition of financial service consumer and people so that consumer protection can be achieved as what expected.   Keywords: Consumer Protection, Financial Service Authority, OJK.